1997
DOI: 10.1074/jbc.272.47.29947
|View full text |Cite
|
Sign up to set email alerts
|

Association of Src Family Tyrosine Kinase Lyn with Ganglioside GD3 in Rat Brain

Abstract: Association of gangliosides with specific proteins in the central nervous system was examined by co-immunoprecipitation with anti-ganglioside antibody. Protein kinase activity was detected in precipitates with monoclonal antibody to ganglioside G D3 (R24) from membranal fraction of rat brain. Using in vitro kinase assay, several phosphorylated proteins of 40, 53, 56, and 80 kDa were isolated by gel electrophoresis. Of these proteins, the proteins of 53 and 56 kDa (p53/56) were identified as two isoforms of Src… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(70 citation statements)
references
References 77 publications
(70 reference statements)
2
68
0
Order By: Relevance
“…It may be significant that GD1a is enriched in these domains (relative to other gangliosides) in CGNs in culture (29). In separate studies, Ab-induced crosslinking of ganglioside GM3 in melanoma cells (43) or GD3 in neurons (44) resulted in activation of raft-resident signaling molecules (Src and Lyn, respectively). These data established a potential functional link between ganglioside crosslinking and intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It may be significant that GD1a is enriched in these domains (relative to other gangliosides) in CGNs in culture (29). In separate studies, Ab-induced crosslinking of ganglioside GM3 in melanoma cells (43) or GD3 in neurons (44) resulted in activation of raft-resident signaling molecules (Src and Lyn, respectively). These data established a potential functional link between ganglioside crosslinking and intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction of non-receptor tyrosine kinases has also been demonstrated in association with several glycosphingolipids. This includes the activation of c-Src by exogenous GM3 (25), the activation of Lyn by anti-ganglioside GD3 antibody (22), activation of Lck with exogenous GM1 (26), the activation of Lyn with anti-␣GalGD1b antibody (27), and the activation of Yes by the globotriaosylceramide binding toxin shiga toxin (23). The mechanism responsible for the regulation of non-receptor tyrosine kinases by glycosphingolipids is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now implicated the association of most every non-receptor tyrosine kinase with glycosphingolipids. These include c-Src (19), Lyk, Fyn (20), Lyn (21,22), Yes (23), Cbl (24), FAK (19), and Csk (25). These studies have either localized these tyrosine kinases in raft fractions by density gradient separations or have coimmunoprecipitated these kinases with anti-glycosphingolipid antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that R24 treatment of primary cerebellar cultures induced Lyn activation and tyrosine phosphorylation of p80 and that Lyn was present in the lipid raft fraction of sucrose density gradient analysis (21). Therefore, we investigated whether tyrosine phosphorylation of p80 was detected in the lipid raft fraction.…”
Section: Identification Of P135 As the Gpi-anchored Neuronal Cell Adhmentioning
confidence: 99%
“…We previously demonstrated that anti-ganglioside GD3 antibody (R24) coimmunoprecipitates the Src family kinase Lyn from the rat cerebellum (21). R24 treatment of primary cerebellar cultures induced Lyn activation and rapid tyrosine phosphorylation of an 80-kDa protein (p80).…”
mentioning
confidence: 99%